Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) di PT. Gamma Mandiri Teknik Menggunakan Metode FMEA - Septiani, Riana; Noverly, Devangga (Fakultas Teknik Universitas Tulang Bawang, 2024)
Work accidents always bring negative impact to the company, so need efforts to minimize the impact on the risks. Apart from causing injuries, work accidents also cause damage to materials, property, facilities and infrastructure. What must be the high light are work accidents that end in injury, so it is hoped that this can reduce the death rate. Identifying potential dangers and risks before and after an accident occurs is an action to prevent accidents. The aim of this research is to determine the potential Occupational health & Safety and risks that occur at the PT Gamma Mandiri Teknik Bina Karya Workshop, assess the greatest potential dangers and risks, and minimize them using the Failure Mode and Effect Analysis Method (FMEA). At PT Gamma Mandiri Teknik, there were found 6 cases of risk and 4 danger factors. With the FMEA method, the largest RPN value is 177.48 or 38.52 percent, which is the risk of burning for the risk of hands and feed burns to welding welding spatter. Keywords: Accident, FMEA, RPN